Morphometric Analysis of Sexual Dimorphism in Foramen Magnum (Medico Legal Update, 2019)
Introduction: The establishment of human sex identity is of paramount importance in the field of forensicmedicine especially when it comes to medico legal cases of disputed sex, completely decomposed or charredbodies, and decapitated cadaveric remains, exhumation of skeletonized remains where skull is recoveredand referred to a forensic expert for opinion by the police, etc.Methodology: Study sample includes 77 dry human skull bones obtained from department of forensicmedicine, department of anatomy and student volunteers of T.O.M.C.H & R.C. T. The sex of the skullbone is estimated by using morphological characteristics. The anterio-posterior diameter and the transversediameter of the foramen magnum is measured using a Vernier caliper. The results are tabulated in MicrosoftExcel 2013 document and the areas of foramen magnum were calculated using the formulae derived byRoutal and Teixeira. Statistical analysis for correlation between the measurements and the sex of the skullwas performed using SPSS software.Results: Majority of skulls belonged to the female sex with maximum distribution in 25 to 35 age groupfollowed by 18 to 25 age group. The length, breadth, and the area of foramen magnum are found to be largerin males than females. However, statistically significant sex differences were observed only for the breadthand areas of the foramen magnum.Discussion: Our findings with regard to the sexing potential of foramen magnum dimensions found astatistically significant difference for breadth of the foramen magnum but the sexual dimorphism index andlogistic regression for the same does not indicate a significant difference. The present research also reportsa statistically significant sex differences in the area of foramen magnum as derived by formula given byTeixeira and Radinsky which is similar to that reported in earlier studies.Conclusion: Parameters analyzed for sexual dimorphism of foramen magnum the area of the foramenmagnum proves to be a better predictor of sex compared to other features but foramen magnum alone shouldnot be considered for sexual differentiation unless the skull is mutilated.